5(x-7)+6=5x-23

Simple and best practice solution for 5(x-7)+6=5x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-7)+6=5x-23 equation:


Simplifying
5(x + -7) + 6 = 5x + -23

Reorder the terms:
5(-7 + x) + 6 = 5x + -23
(-7 * 5 + x * 5) + 6 = 5x + -23
(-35 + 5x) + 6 = 5x + -23

Reorder the terms:
-35 + 6 + 5x = 5x + -23

Combine like terms: -35 + 6 = -29
-29 + 5x = 5x + -23

Reorder the terms:
-29 + 5x = -23 + 5x

Add '-5x' to each side of the equation.
-29 + 5x + -5x = -23 + 5x + -5x

Combine like terms: 5x + -5x = 0
-29 + 0 = -23 + 5x + -5x
-29 = -23 + 5x + -5x

Combine like terms: 5x + -5x = 0
-29 = -23 + 0
-29 = -23

Solving
-29 = -23

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (2x+3)*(4x+7)=8x^2-5 | | X+(X+55)+(X+38)=180 | | 14/5x−14=4/5x−7/4 | | 12=7m-1+6m | | U=2a+2b | | X+3x-4=5(x+2) | | 6y-2=20 | | 18(2x+6)=6(3x+30) | | 40p-5=-5p-5 | | lne^4/5 | | 3x+7+5x=11+4x+8 | | 2x-6x=-2x | | 26+X^2=90 | | 6x^3+2x^2=10x-8 | | 5.8(x-4)=0.2x+24.8 | | -d+5=20 | | -6=1/3x-4 | | -350.55555556/1.8 | | 0.02x=x-12.25 | | 13x+32-9x=-24-4x | | 2(t-4)+9=-7 | | -631/1.8 | | -10+a=10 | | 6(4x-3)-(2+x)=55-2x | | -y+8=38 | | 8(8-4x)=-192 | | 2(2x+3)=21 | | H(x)=xsquared-8x+3 | | 2x+3-9x=25-7x | | 3(x-5)+8x=62+4x | | -3=m/9 | | -c+7=52 |

Equations solver categories